2008
DOI: 10.1007/s10529-008-9659-8
|View full text |Cite
|
Sign up to set email alerts
|

Production, characterization and (co-)immobilization of dextranase from Penicillium aculeatum

Abstract: Fermentation kinetics of Penicillium aculeatum ATCC 10409 demonstrated that fungal growth and dextranase release are decoupled. Inoculation by conidia or mycelia resulted in identical kinetics. Two new isoenzymes of the dextranase were characterized regarding their kinetic constants, pI, MW, activation energy and stabilities. The larger enzyme was 3-fold more active (turnover number: 2,230 +/- 97 s(-1)). Pre-treatment of bentonite with H(2)O(2) did not affect adsorption characteristics of dextranase. Enzyme to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…; Penicillium pinophilum, Penicillium aculeatum, and Eupenicillium javanicum which were isolated in this work had not according to the literature been involved in skin infection. They had been reported to be frequently isolated from soil and are involved in the production and saccharification of different industrial enzymes like B-Dmannase, endoglucanase, -glucosidase, and pectinase and in saccharification of polysaccharides of barley, oat and wheat straw, and Solka-Floc [33][34][35][36]. The ability of these organisms to produce the abovementioned enzymes could explain their ability to also degrade the keratinized areas of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…; Penicillium pinophilum, Penicillium aculeatum, and Eupenicillium javanicum which were isolated in this work had not according to the literature been involved in skin infection. They had been reported to be frequently isolated from soil and are involved in the production and saccharification of different industrial enzymes like B-Dmannase, endoglucanase, -glucosidase, and pectinase and in saccharification of polysaccharides of barley, oat and wheat straw, and Solka-Floc [33][34][35][36]. The ability of these organisms to produce the abovementioned enzymes could explain their ability to also degrade the keratinized areas of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…), Bradford reagent, dopamine hydrochloride, and glutaraldehyde were purchased from Sigma-Aldrich. According to the study of Erhardt et al, the activity of immobilized enzyme retains in a high level for 20 days without any decrease [31]. The accumulation of substrates on the membrane surface causes a low enzyme/substrate ratio, thus the enzymes need longer time to convert the substrates to small sized oligodextran products [8].…”
Section: Methodsmentioning
confidence: 99%
“…Maximum dextranase production at 30°C was also reported by Koenig and Day (1988) from Lipomyces starkeyi and Abdel-Aziz et al (2007) from a new strain of Penicillium funiculosum. However, according to Erhardt et al (2008) maximum production of dextranase (60 U/ml) was observed at 26°C from Penicillium aculeatum.…”
Section: Fig 1 Effect Of Initial Ph Of Culture Medium On Dextranase mentioning
confidence: 97%